ANALYSIS OF RELATIONS BETWEEN JUDO TECHNIQUES AND SPECIFIC MOTOR ABILITIES - Patrik Drid (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Specific physical preparation affects the development of motor abilities required for execution of specific movements in judo. When selecting proper specific exercises for judo for a target motor ability, it is necessary to precede it with the study of the structure of specific judo techniques and activities of individual muscle groups engaged for execution of the technique. On the basis of this, one can understand which muscles are most engaged during realization of individual techniques, which serves as a standpoint for selection of a particular complex of specific exercises to produce the highest effects. In addition to the development of particular muscle groups, the means of specific preparation will take effect on the development of those motor abilities which are evaluated as the indispensable for the development of particular qualities which are characteristic for judo. This paper analyses the relationship between judo techniques field and specific motor abilities.